Tissue Viability of Free Flaps after Extracorporeal Perfusion Using a Modified Hydroxyethyl Starch Solution - Taeger, Christian D.; Friedrich, Oliver; Horch, Raymund E.; Distler, Caroline; Kengelbach-Weigand, Annika; Wenzel, Carina; Prantl, Lukas; Präbst, Konstantin (Journal of Clinical Medicine, 2020)
Background: In free flap surgery, tissue is stored under hypothermic ischemia. Extracorporeal perfusion (EP) has the potential to extend storage time and the tissue's perspective of survival. In the present study, the aim is to improve a recently established, simplified extracorporeal perfusion system. Methods: Porcine musculus rectus abdominis were stored under different conditions. One group was perfused continuously with a simplified one-way perfusion system for six hours, while the other received only a single flush but no further treatment. A modified hydroxyethyl starch solution was used as a perfusion and flushing solution. Vitality, functionality, and metabolic activity of both groups were analyzed. Results: Perfused muscles, in contrast to the ischemically stored ones, showed no loss of vitality and significantly less functionality loss, confirming the superiority of storage under continuous perfusion over ischemic storage. Furthermore, in comparison to a previous study, the results were improved even further by using a modified hydroxyethyl starch solution. Conclusion: The use of EP has major benefits compared to the clinical standard static storage at room temperature. Continuous perfusion not only maintains the oxygen and nutrient supply but also removes toxic metabolites formed due to inadequate storage conditions.
CRIS-Team WoS Importer:2021-01-08